1994
DOI: 10.1093/nar/22.5.711
|View full text |Cite
|
Sign up to set email alerts
|

The DNA binding domains of the varicella-zoster virus gene 62 and herpes simplex virus type 1 ICP4 transactivator proteins heterodimerize and bind to DNA

Abstract: The product of varicella-zoster virus gene 62 (VZV 140k) is the functional counterpart of the major transcriptional regulatory protein of herpes simplex virus type 1 (HSV-1), ICP4. We have found that the purified bacterially expressed DNA binding domain of VZV 140k (residues 417-647) is a stable dimer in solution. As demonstrated by the appearance of a novel protein--DNA complex of intermediate mobility in gel retardation assays, following in vitro co-translation of a pair of differently sized VZV 140k DNA bin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0
1

Year Published

1998
1998
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 58 publications
(63 reference statements)
0
13
0
1
Order By: Relevance
“…Two ocular-derived CD4 TCC recognize VZV peptide IE62 918-927 using discordant HLA-DR alleles and TCR Two protein domains of VZV IE62 and the orthologous HSV-1 protein ICP4 are highly conserved among alphaherpesvirinae: a domain that contains sites for DNA binding and homodimerization (IE62 463-636 and ICP4 ) and the large C-terminal region (IE62 750-1187 and ICP4 ) involved in transactivation of virus genes (28,40). Previously, we reported that IE62 is a common target Ag of the intraocular VZV-specific T cell response in VZV uveitis patients (18).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two ocular-derived CD4 TCC recognize VZV peptide IE62 918-927 using discordant HLA-DR alleles and TCR Two protein domains of VZV IE62 and the orthologous HSV-1 protein ICP4 are highly conserved among alphaherpesvirinae: a domain that contains sites for DNA binding and homodimerization (IE62 463-636 and ICP4 ) and the large C-terminal region (IE62 750-1187 and ICP4 ) involved in transactivation of virus genes (28,40). Previously, we reported that IE62 is a common target Ag of the intraocular VZV-specific T cell response in VZV uveitis patients (18).…”
Section: Resultsmentioning
confidence: 99%
“…VZV IE62 and HSV ICP4 are abundantly expressed viral proteins that are transported from the nucleus to the cytoplasm for incorporation in the tegument of the virion during lytic infection (27,(60)(61)(62). Both viral proteins are large (∼1300 aa long) and contain a DNA binding and a large C-terminal transactivator domain that are both highly conserved among alphaherpesvirinae of diverse animal species (28,40,63). Previous studies showed that viral tegument proteins, including VZV IE62 and HSV-1 ICP4, are immunoprevalent targets of aHHV-specific CD4 and CD8 T cells in blood of healthy HSV-1-and/or VZV-infected adults (29,(64)(65)(66), lesions of genital herpes patients (67), affected eyes of herpetic uveitis and keratitis patients (18)(19)(20)68), and at the site of HSV-1 latency in human trigeminal ganglia (69).…”
Section: Discussionmentioning
confidence: 99%
“…Or, tout activateur transcriptionnel possède, en général, plusieurs domaines fonctionnels : un domaine de fixation à l'ADN, un domaine activateur et un signal de localisation nucléaire (figure 3). L'ensemble de la région 2 de l'IE62, et plus particulièrement les acides aminés 472 à 633, possède des propriétés de fixation à l'ADN et s'y fixe sous forme de dimères [19]. Une séquence, identifiée à l'intérieur du domaine de fixation à l'ADN pré-sente des similitudes frappantes avec l'hélice de l'homéodomaine reconnaissant l'ADN.…”
Section: Résidus Appelée Ie62 (175 Kda) Celle-ci Présente De Fortes unclassified
“…The protein is 1,310 amino acids in length and contains a potent N-terminal acidic activation domain and a centrally located DNA binding domain. It is believed to be a native homodimer, based on comparison with its putative homolog HSV-1 ICP4 and the experimentally established dimerization of a bacterially expressed fragment containing the DNA-binding domain and sequences corresponding to the ICP4 dimerization domain (50).…”
mentioning
confidence: 99%
“…The IE62 DBD was also shown to interact with this sequence within the ICP4-binding sites present in the HSV ICP4 and gD promoters. Site-specific mutation of each nucleotide within the ICP4 consensus site showed that only mutations within the 5Ј ATCGT sequence affected IE62 DBD binding, whereas mutations in both the 5Ј and 3Ј sequences affected ICP4 binding (4,48,49,50). Tyler and Everett (49) showed that the DBD fragment interacted with several sequences within the ORF62 promoter, including three ATCGT consensus sites.…”
mentioning
confidence: 99%